Psychoeducation as an effort to reduce stunting rates in Genikan Village - Nanda Kusuma Wardani; Fredirikus Bayu Kurniawan; Anggi Nur Alifah; Farenanda Kusuma Wardani; Hemalia Astikawati; Rayinda Faizah (Community Empowerment, 2022)
According to Nutrition Status Monitoring (PSG) data from Magelang Regency in 2018, 38.3% of children under the age of five were stunted. In comparison to 2017 (32.51%) and 2016 (14.30%), this figure has risen. The main goal of this program is to reduce stunting rates through parenting, nutrition, and early marriage programs. Counseling on nutrition, psychoeducation on healthy parenting, psychoeducation on the risks of early marriage and marriage preparation to build a healthy family, and play for children are among the programs offered. Village officials and local midwives are involved in the implementation of this program, which takes place in the Genikan Village’s multipurpose building. On the basis of the activities' implementation, it can be concluded that the community service activities in Genikan Village are proceeding as planned. Every program that has been prepared has a good chance of being implemented successfully and receiving positive feedback from the local community. In order to reduce stunting rates in Genikan Village, it is hoped that all of the programs that have been implemented will be useful and provide additional knowledge to the community.